2010
DOI: 10.1175/2010jas3389.1
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Observation of Post-Cold-Frontal Continental Stratocumulus

Abstract: More studies on the dynamics of marine stratus and stratocumulus clouds have been performed than comparable studies on continental stratocumulus. Therefore, to increase the number of observations of continental stratocumulus and to compare marine and continental stratocumulus to each other, the approach of large-eddy observation (LEO) was applied to a case of nocturnal continental stratocumulus observed over the Atmospheric Radiation Measurement Program (ARM) Climate Research Facility (ACRF) in the central Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
4
7
2
Order By: Relevance
“…In our simulations, the surface latent heat flux is fixed, but the surface layer was also decoupled from the sub‐cloud layer so that changes in the surface fluxes had limited influence on the stratocumulus cloud properties (simulations LH0 and LH30). These results were similar to those found in Mechem et al (). However, the surface latent heat flux was an important parameter for the lower fog layer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our simulations, the surface latent heat flux is fixed, but the surface layer was also decoupled from the sub‐cloud layer so that changes in the surface fluxes had limited influence on the stratocumulus cloud properties (simulations LH0 and LH30). These results were similar to those found in Mechem et al (). However, the surface latent heat flux was an important parameter for the lower fog layer.…”
Section: Discussionsupporting
confidence: 93%
“…A surface-based inversion up to 250 m was initially present, below a capping inversion between 950 and 1200 m. The ice/liquid potential temperature jump across the upper inversion was about 5 K. The layer between the two inversions was well mixed. Note that the initial total moisture profile does not display a clear 'moisture jump' across the cloudtop inversion, which is consistent with previous studies of continental stratocumulus (Mechem et al, 2010;Fang et al, 2014;Ghate et al, 2014) but different from the environment of typical marine stratocumulus clouds (Wood, 2012). Marine stratocumulus clouds are often found in strong subsidence regions associated with the descending branch of the Hadley cell circulation.…”
Section: Initial Conditions and Forcings For The Baseline Simulationsupporting
confidence: 90%
“…Previous investigations of aerosol impacts on low-level Sc have focused overwhelmingly on marine cloud systems, which are generally controlled by very different dynamical processes compared to systems over land (Mechem et al, 2010;Wood, 2012). The preliminary results from aerosol sensitivity simulations presented herein revealed the familiar response of increased numbers and smaller sizes of cloud droplets with increasing aerosol concentrations, whereas increases in LWP and cloud optical depth were mostly opposite to findings from previous studies on marine Sc.…”
Section: Concluding Remarks and Future Workcontrasting
confidence: 64%
“…For example, Mechem et al (2010a) observed that cloud layer circulations in post-frontal Sc over land are driven by cloud top radiative cooling similar to marine Sc, yet the former exhibited weaker turbulence structures than in their marine counterparts. Additionally, simulations of post-frontal Sc over land using a LES model revealed advection of temperature and moisture were governing factors over system maintenance and decay as opposed to entrainment or surface fluxes as in marine Sc (Mechem et al, 2010b).…”
Section: Challenges and Perspectivesmentioning
confidence: 99%